(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce the notion of pseudo BN-algebras and investigate some of its basic properties. Moreover, its relationship with the already established pseudo BF-algebra is investigated. Furthermore, subalgebras, ideals and pseudo-normality of pseudo BN-algebras are studied. Illustrations are provided for new concepts. Finally, we establish the equivalency of pseudo-normal subalgebras and pseudo-normal ideals.